Psychosocial problem and its associated factors among adolescents in the secondary schools in Pasir Gudang, Johor - Abdul Latiff, Latiffah; Tajik, Esra; Ibrahim, Normala; Abu Bakar, Azrin Shah; Albar Ali, Shirin Shameema (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Adolescence is a crucial period with impressive emotional changes. Emotional disorders such as depression, anxiety and stress are high among adolescents worldwide; however the psychosocial changes are often neglected. The aim of the current study was to determine the depression, anxiety and stress symptoms and their associated factors among adolescents. Methods: A cross-sectional study using cluster sampling was carried out among school-going adolescents in 10 secondary schools in Pasir Gudang, Johor, Malaysia. Respondents answered a self-administered questionnaire including socio-demographic, Inventory of Parent and Peer Attachment (IPPA), Depression Anxiety Stress Scale-21 (DASS-21) and Strength and Difficulties Questionnaire (SDQ). Using SPSS-21, chi-square test and binomial logistic regression were conducted to examine the associations between dependent and independent variables. Results: Respondents (52.6% female and 53.9% Malay) had 46.0% prevalence of depression symptoms, 59.1% anxiety, 38.1% stress and 45.6% psychosocial status (internalizing and externalizing problems). Age, father occupation and parental bonding were significantly predicted having moderate to extremely severe depression symptom (p<0.05). Younger adolescents (13-14 years old) were 1.42 times more likely to have anxiety symptom. In addition, respondents with insecure father attachment were 1.5 times more likely to have stress symptom (p<0.05). Respondents with insecure parental attachment were more likely to have psychosocial problem (p<0.05). Conclusions: Depression, anxiety and stress of adolescents were influenced by the sociodemographic of adolescents and their parents. Age, gender and parental attachment were the significant predictors in the current study which should be the center of attention for the future studies to reduce the psychological disorders among adolescents.